RELEASE OF VASOPRESSIN DURING SUPPRESSION OF THE OESTROUS CYCLE IN THE RAT BY TAMOXIFEN AND HYPEROSMOTIC OR HYPOVOLEMIC CHALLENGES - Kundi, Salma Aslam; Forsling, Mary; Kelestimur, Haluck (Journal of Ayub Medical College Abbottabad, 1989)
ABSTRACT Previous studies have shown that surgical ovariectomy of the rat results in a fall in the plasma visopressin concentrations suggesting that ovarian steroids may influence hormone release and after surgical ovariectomy the response to hypertonicity was unaffected but that to hypovolemia was attenuated. To determine whether a similar fall is observed on suppression of the oestrous cycle, vasopressin concentrations were monitored after treatment with the antiestrogen preparation tamoxifen. Treatment with tamoxifen was found to result in a fall in circulating vasopressin concentrations, with little effect on fluid balance. To determine whether the ovary could influence the vasopressin release in response to known stimuli, hormone concentrations were measured in tamoxifen ovarectomized rats during extracellular fluid hypertonicity produced by Intra-peritoneal (i.p.) injection of hypertonic saline and hypovolemia produced by i.p. injection of polyethylene glycol. It was found that after treatment with tamoxifen, the response to hypertonicity was unaffected but that to hypovolemia was attenuated. Hence tamoxifen is a potent anti-estrogen drug, and tamoxifen ovariectomized rats behaved in the same manner as surgically ovariectomized rats.